Role socialization family erroneous and its impact on criminal behavior (Journal of the College of Education for Women, 2019)
The correct and sincere process of socialization is working on appropriate social climate inwhich this process is the provision, and the climate is achieved in the presence of a positiveenvironment free of negatives and contradictions, but when there is a socialization processesinadequate and contradictory was not based on the principles of punishment and reward nor abalance between methods soft and intensity of treatment and interaction with small andadolescent does not require intensive social care formulas do not create the conditionsessential items required by the successful and effective socialization, the young and the youngpeople who are going through in such Altanisah and educational operations will be subject tobehavioral and interactive distractions that may lead them to the behavioral and interactiveacts intersecting with the laws and values and ideals and standards of society, and here theyoung and the young people are not exposed to damage, but exposed them community also aslong as the repercussions of the crime does not affect the criminals alone but affects theircommunity and great community, as a n any defect or problem exposed passes through thestages of socialization small five Kalmrahlh oral or anal sexual or adolescence or maturity orcompleteness commute or divorce his mother hibernate during sexual hibernation stage oradolescence or neglect and indifference to the subject of his education and hone his talentsand school collected or mixing with children of bad and deviants and perverts of his peers, allof that cause deviations and behavioral problems adversely affect the daily interactions andthe degree of adaptation balanced with the social environment, and this may led todelinquency and crime or commit acts Hena and intersecting with the laws of society andbehavioral and interactive contexts.